Impact of iron exposure on Brazilian coral reefs: Acute vs. chronic stress responses - Letícia May Fukushima; Juliana da Silva Fonseca; Thales Jean Vidal; Kely Paula Salvi; Carlos Henrique Figueiredo Lacerda; Patrícia Gomes Costa; Miguel Mies; Adalto Bianchini (Ecotoxicology and Environmental Safety)
Prior research has shown that exposure to metals increases corals vulnerability to bleaching by heightened oxidative stress. Understanding the impact of metal contamination on coral health in their natural environmental is crucial. This study investigate the effects of iron (Fe) exposure on Brazilian coral reef species. We evaluated the response of Mussismilia harttii, Millepora alcicornis, and Siderastrea sp. to acute (4 days) and chronic (28 days) Fe exposure under environmentally relevant concentrations (0, 100, 300 and 900 μg L−1). Experiments were conducted in laboratory and in a marine mesocosm Biomarkers including Fe bioaccumulation, lipid peroxidation (LPO), protein carbonylation (PCN), and DNA damage were measured. The correlation between chronic exposure results and environmental factors were also analyzed. The hypotheses were: a) Fe exposure would increase ROS production in corals, leading to biomolecule damage; b) acute and chronic Fe exposure would affect ROS production and biomolecule damage differently; c) Fe bioaccumulation would vary between species and concentrations; and d) environmental factors might influence coral responses to Fe. Results indicated that all species exhibited increased Fe bioaccumulation as metal concentrations increased, suggesting a common ability to absorb and accumulate Fe. The oxidative damage response vired between acute and chronic exposure, with acute exposure causing more damage while chronic exposure showed a temporal reduction in damage. Environmental factors (e.g. temperature, pH, salinity and dissolved oxygen) also influenced the coral responses, either exacerbating or mitigating oxidative stress effects. These findings highlight the importance of understanding Fe contamination impacts for the conservation of Brazilian coral reefs.